2014
DOI: 10.1002/pen.24039
|View full text |Cite
|
Sign up to set email alerts
|

Extrusion film casting of long chain branched polypropylene

Abstract: Extrusion film casting (EFC) is an important melt processing operation which is extensively used to make polypropylene (PP) films. Linear PP shows significant amount of necking and draw resonance during EFC. One of the ways to reduce necking is to introduce long chain branches (LCB) on the polymer backbone. The long branches impart extensional strain hardening behavior thereby stabilizing the melt flow. In this work, we investigate the influence of long chain branching in polypropylene on the extent of necking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 43 publications
(70 reference statements)
1
24
0
Order By: Relevance
“…There has also been done a considerable amount of work on EFC under the non-isothermal conditions by Lamberti et al [18][19][20], Lamberti and Titomanlio [21][22][23][24], and Titomanlio [25]. Recently, Pol et al [26,27] and Chikhalikar et al [28] have published a series of articles investigating the influence of the polymer molecular structure on the necking development. For this purpose they utilized the 1D membrane model, originally proposed by Silagy et al [14], the multimode eXtended Pom-Pom constitutive equation and the multimode Rolie-Poly stretch constitutive equation,…”
Section: Introductionmentioning
confidence: 99%
“…There has also been done a considerable amount of work on EFC under the non-isothermal conditions by Lamberti et al [18][19][20], Lamberti and Titomanlio [21][22][23][24], and Titomanlio [25]. Recently, Pol et al [26,27] and Chikhalikar et al [28] have published a series of articles investigating the influence of the polymer molecular structure on the necking development. For this purpose they utilized the 1D membrane model, originally proposed by Silagy et al [14], the multimode eXtended Pom-Pom constitutive equation and the multimode Rolie-Poly stretch constitutive equation,…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of long chain branching structure into polymer is proved to be an efficient way to enhance its matrix strength, [17][18][19][20] which could benet the scCO 2 foaming of polymer. [20][21][22] It was found that the long-chain branching structure decreased the degree of coalescence in polymers, and the higher cell density was observed in branched polymers due to its enhanced melt strength.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few years, different basic concepts have been studied in the literature to achieve high melt strength PP (PP-HMS) using different methods [5][6][7][8][9]. According to Chikalikar et al [10], it is possible to increase the melt strength of PP in different ways:…”
mentioning
confidence: 99%